Additives in Plasticised Polyvinyl Chloride Fuel Microbial Nitrate Reduction at High pH: Implications for Nuclear Waste Disposal - Nixon, Sophie L.; van Dongen, Bart E.; Boothman, Chris; Small, Joe S.; Lloyd, Jonathan R. (Frontiers in Environmental Science, 2018)
The safe disposal of nuclear waste necessitates a thorough understanding of the role microorganisms play on the fate of the waste materials over time. Despite significant volumetric contributions to nuclear waste inventories, little is known about the fate of plastics under the high pH and irradiating conditions of a geological repository. We conducted microbial enrichment experiments to assess the potential for additives in plasticised polyvinyl chloride (PVC) sheet, commonly used in the nuclear industry, to fuel nitrate reduction by a microbial community adapted to grow at pH 10. These additives include plasticisers and flame retardants, amongst others. PVC powder (no additives) served as an additive-free control, and samples of both materials were gamma irradiated (1 MGy) under hyperalkaline conditions, representative of conditioned nuclear waste, to assess the effect of irradiation on bioavailability. Plasticised PVC supported near-complete nitrate reduction, whether irradiated or not, although irradiated PVC sheet supported less nitrate reduction. No nitrate reduction was observed with non-irradiated PVC powder, although irradiated powder supported minor nitrate reduction. These results highlight the bioavailability of volumetrically significant plasticised PVC under conditions relevant to its geological disposal in cementitious intermediate level nuclear waste and highlight the critical need to constrain downstream effects on biogeochemical processes ultimately impacting on the safety case for disposal.